Postoperative outcomes of oblique osteotomy and capsuloplasty for the treatment of bunionette in the fifth metatarsal neck - Greenhalgh Dias Fernandes Júnior; Joaquim Maluf Neto; Carlos Augusto Silva de Andrade; Auro Mtsuo Okamoto; Danyel Selleguim Laghi; Rodrigo Saraiva Marquez (Journal of the Foot & Ankle, 2022)
Objective: Present the outcomes of oblique osteotomy and capsuloplasty based on the pre-/postoperative American Orthopaedic Foot & Ankle Society (AOFAS) scores and demonstrate the possibility of correcting all four types of bunionette through a single technique. Methods: Descriptive observational study performed through medical records assessment based on the pre-/postoperative AOFAS scores. Results: Fifty-three feet were operated on, 28 on the right side and 25 on the left, predominantly female (n=34) and one male. The mean age was 44.8 years (range 19-77). The improvement in the AOFAS score occurred in all patients, the preoperative mean was 53.7 (44-57), and the postoperative mean was 77.4 (65-80). The distal oblique osteotomy of the fifth metatarsal associated with capsuloplasty was used. Conclusion: The technique used in our study presents a significant improvement in all cases, corroborating with the outcomes in the literature. Level of Evidence IV; Descriptive Observational Study.